Forming Ecomasculinities through Deep Ecology in Gravity's Rainbow - Addis, Victoria (The Trumpeter)

(untitled) (Athabasca University Press, 2020)
This article examines the concept of ecomasculinity--how masculinities and ecologies interact--through the lens of deep ecology, arguing (following Serpil Oppermann) that Pynchon's postmodernist boundary collapsing informs deep-ecological interconnections for male characters previously embroiled in negative cycles of patriarchal dominance. Ecomasculinity is an important emerging concept within ecocriticism, and recognising links between the positive iterations of masculinity and ecology that the ecomasculine seeks to express and the philosophy of deep ecology furthers the conversation about the utility of deep ecology to contemporary society.